2013
DOI: 10.2527/jas.2013-6400
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in ovo injection of carbohydrate solution on small intestine development in domestic pigeons (Columba livia)1

Abstract: The objective of this study was to test the hypothesis that in ovo injection of carbohydrates into pigeon (Columba livia) amnion may improve the small intestine development. At d 14.5 of incubation, 80 fertile eggs were injected with 200 μL of carbohydrate solution, and 80 control eggs were not injected. The carbohydrate solution (wt/vol) contained 2.5% maltose + 2.5% sucrose, all dissolved in 0.75% saline. Twelve eggs from each treatment were randomly sampled at d 16 of incubation and the day of hatch, embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…Our results showed that IOF of Arg had a 1.5‐fold increase in duodenal AKP activity than other groups, suggesting that IOF of Arg contributed to improving the gut health and digestive‐absorptive function of small intestine. In parallel with the studies described above, Dong, Wang, Song, and Zou () reported that IOF of carbohydrate solution exhibited significantly greater activities of sucrase, maltase and AKP in jejunum of pigeons from 16 days of incubation to hatching day than the control group.…”
Section: Discussionsupporting
confidence: 59%
“…Our results showed that IOF of Arg had a 1.5‐fold increase in duodenal AKP activity than other groups, suggesting that IOF of Arg contributed to improving the gut health and digestive‐absorptive function of small intestine. In parallel with the studies described above, Dong, Wang, Song, and Zou () reported that IOF of carbohydrate solution exhibited significantly greater activities of sucrase, maltase and AKP in jejunum of pigeons from 16 days of incubation to hatching day than the control group.…”
Section: Discussionsupporting
confidence: 59%
“…If the embryo consumes all the energy sources in the first days of incubation, it will suffer from its deficiency in the last stages of incubation. Energy deficiency can result in a weak hatchling and even embryonic death . Therefore, a stable and sufficient energy status is necessary for the late‐term stage of chick embryos, which can be supplied by the in ovo injection of carbohydrates to the amnion of the late‐term avian embryo .…”
Section: Applications Of In Ovo Technology For Various Biological Supmentioning
confidence: 99%
“…Energy deficiency can result in a weak hatchling and even embryonic death. 76 Therefore, a stable and sufficient energy status is necessary for the late-term stage of chick embryos, which can be supplied by the in ovo injection of carbohydrates to the amnion of the late-term avian embryo. 77,78 Many previous studies have confirmed that the energy status or BW of hatchlings had improved in response to the in ovo injection of carbohydrate solutions, including glucose, maltose, sucrose, or dextrin, singly or in combination with other nutrients.…”
Section: Carbohydratesmentioning
confidence: 99%
“…In ovo feeding (IOF), the injection of exogenous nutrients into the amnion of developing embryos of oviparous species may serve as a tool to enhance subsequent pre‐hatching functioning and post‐hatching growth and/or to overcome a delay in post‐hatching enteric maturation (Kadam et al., ) due to impaired digestive capacity that is caused by early, post‐natal underfeeding or feed deprivation (Kornasio et al., ). Recent researches showed that in ovo administration of amino acids such as beta‐hydroxy‐beta‐methylbutyrate (leucine metabolite) (Kornasio et al., ), threonine (Kadam et al., ), and arginine (Tangara et al., ), or a mixture of amino acids (Uni et al., ) or carbohydrates (Dong et al., ) regulates body weight (Kadam et al., ; Dong et al., ), energy metabolism (Tangara et al., ), digestive function (Dong et al., ), and immunological responses (Kadam et al., ) during hatching or in later life. However, there is still little information about the impact of IOF of such substances on post‐hatching muscle growth.…”
Section: Introductionmentioning
confidence: 99%